Histopathological and Haematological Manifestations of Typhoid Fever in Pediatric Age Group - Faiza Rafiq, Faiza Shafqat, Zertaj Kahif, Manqoosh Ur Rehman, Sehar Shamshad Ali, Sonia Zafar Warriach, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Typhoid fever is an acute systemic infection caused by Salmonella Enterica Serovar Typhi. Organism is transmitted by fecal-oral route. Aim: To determine frequency of various histopathological & hematological manifestations of typhoid fever in pediatric age group. Study design: Cross-sectional survey. Methodology: Complete blood count, pro-thrombin time and activated partial thromboplastin time were performed on the patients (n=140) to find out various hematological manifestations. Histopathological findings of patients undergoing colonoscopy and biopsy due to gastrointestinal presentations were also noted. Results: Present study had 65% males with 35% females. Almost 65.7% cases presented with anemia. Around 50.7% patients had leucopenia while eosinopenia was 67.1%. Cases (39.3%) presented with prolonged activated partial thromboplastin time while 32.1% cases had prolonged pro-thrombin time. Among histopathological manifestation, 3(2.14%) presented with Typhoid colitis/enteritis, 2(1.43%) with gastrointestinal bleeding due to ulcers and only 1(0.71%) with peritonitis. Conclusion: It was concluded that most common haematological manifestation in typhoid fever was eosinopenia which was most frequently found in coexistence with thrombocytopenia. However, histopathological abdominal complications were quite rare but could be dreadful and should be kept in mind.